Comparison of Outcomes for Children With Cervical Spine Injury Based on Destination Hospital From Scene of Injury. (January 2014) - Anders, Jennifer F.; Adelgais, Kathleen; Hoyle, John D.; Olsen, Cody; Jaffe, David M.; Leonard, Julie C.; ,; Gratton MD, Matthew C.
Abstract Background Pediatric cervical spine injury is rare. As a result, evidence‐based guidance for prehospital triage of children with suspected cervical spine injuries is limited. The effects of transport time and secondary transfer for specialty care have not previously been examined in the subset of children with cervical spine injuries. Objectives The primary objective was to determine if prehospital destination choice affects outcomes for children with cervical spine injuries. The secondary objectives were to describe prehospital and local hospital interventions for children ultimately transferred to pediatric trauma centers for definitive care of cervical spine injuries. Methods The authors searched the Pediatric Emergency Care Applied Research Network (PECARN) cervical spine injury data set for children transported by emergency medical services (EMS) from scene of injury. Neurologic outcomes in children with cervical spine injuries transported directly to pediatric trauma centers were compared with those transported to local hospitals and later transferred to pediatric trauma centers, adjusting for injury severity, indicated by altered mental status, focal neurologic deficits, and substantial comorbid injuries. In addition, transport times and interventions provided in the prehospital, local hospital, and pediatric trauma center settings were compared. Multiple imputation was used to handle missing data. Results The PECARN cervical spine injury cohort contains 364 patients transported from scene of injury by EMS. A total of 321 met our inclusion criteria. Of these, 180 were transported directly to pediatric trauma centers, and 141 were transported to local hospitals and later transferred. After adjustments for injury severity, odds of a normal outcome versus death or persistent neurologic deficit were higher for patients transported directly to pediatric trauma centers (odds ratio [OR] = 1.89, 95% confidence interval [CI] = 1.03 to 3.47). EMS transport times to first hospital did not differ and did not affect outcomes. Prehospital analgesia was very infrequent. Conclusions Initial destination from scene (pediatric trauma center vs. local hospital) appears to be associated with neurologic outcome of children with cervical spine injuries. Markers of injury severity (altered mental status and focal neurologic findings) are important predictors of poor outcome in children with cervical spine injuries and should remain the primary guide for prehospital triage to designated trauma centers.